Odpowiedź :
wzory Viete'a mają postać.
[tex]\displaystyle {\begin{cases}x_{1}+x_{2}=-{\tfrac {b}{a}}\\x_{1}x_{2}={\tfrac {c}{a}}\end{cases}}[/tex]
gdy mamy jedno rozwiązanie wtedy:
[tex]x_1=x_2=x_0[/tex]
czyli za [tex]x_1\;i\;x_2[/tex] podstawiamy [tex]x_0[/tex]
i wychodzi:
[tex]\displaystyle {\begin{cases}x_{0}+x_{0}=-{\tfrac {b}{a}}\\x_{0}x_{0}={\tfrac {c}{a}}\end{cases}}\\\boxed{\displaystyle {\begin{cases}2x_{0}=-{\tfrac {b}{a}}\\x_{0}^2={\tfrac {c}{a}}\end{cases}}}[/tex]
Dane jest rownanie kwadratowe : ax²+bx+c=0 ,a≠0 ,takie,że Δ=0 .
Wtedy :
x1=x2=xo
Czyli :
2xo=-b/2
(xo)²=c/a